Analysing learning designs of 'learning through practice' as Networked Learning - Hansen, Jens Jørgen; Dohn, Nina Bonderup (Proceedings of the International Conference on Networked Learning, 2018)
Our aim in this paper is to analyse a set of well-known pedagogical approaches based on 'learning through practice' by viewing them as forms of networked learning. Following earlier work by the second author, we understand networked learning as learners' connecting of contexts in which they participate and as their resituation of knowledge, perspectives, and ways of acting across these contexts (Dohn, 2014). Learning designs of 'learning through practice' are distinguished by engaging practices outside the formal educational system as ways of developing curricular understanding and, reciprocally, as providing grounds for concretisation of curricular content through its enactment in practice. By viewing these learning designs as networked learning we highlight their potential for supporting certain connection forms between learners' experiences in target practice and educational practice. In particular, we look at the learning designs of 1) case-based learning, 2) design-based learning, and 3) simulation-based learning. We understand a learning design in accordance with Mor, Mellar, Warburton, & Winters (2014) as an educational pattern that supports specific actions in typical situations and, in compact form, collects the central part of a practice that can be communicated to others (2014). We understand a learning design to have four primary dimensions: 1) purpose, 2) content, 3) methods, and 4) underlying learning-theoretical basis. The four dimensions reflect basic functions of an educational practice: its purpose (its why), its content (its what), its method (its how), and its theoretical basis (its reason for the why, what and how). We argue that case-based learning establishes a relationship of inquiry between learner and target practice with the aim to support the learners in gaining understanding through participating in a sense-making process. The relationship established in design-based learning is one of innovation with the aim to support learners in developing understanding of practice through changing it. Finally, in simulation-based learning, relationships of imitation of target practice and engagement in ‘as-if’ practice are established with the aim of supporting learners in developing situated skills and knowledge.